2021
DOI: 10.1155/2021/5522229
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Intervention on Improvement of Breastfeeding Self-Efficacy: A Systematic Review and Meta-Analysis

Abstract: Background. Self-efficacy is an important psychological and motivational factor in breastfeeding, and it is a valuable framework that predicts breastfeeding outcomes and demonstrates maternal confidence in breastfeeding. The meta-analysis evaluated the effectiveness of educational interventions on improving breastfeeding self-efficacy (BSE). Methods. The English and Persian databases including Medline, Embase, Cochrane Database of Systematic Reviews (CDSR), PubMed, Web of Science, Scopus, CINAHL, Sid, IRANDOC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…Furthermore, the strong focus on breastfeeding, seen in the domain‐specific studies, implies that breastfeeding is critical for gaining confidence in parenting. The focus on breastfeeding mirrors the number of reviews regarding breastfeeding SE based on quantitative studies—such as Galipeau et al ( 2018 ), Gonzales ( 2021 ), Maleki et al ( 2021 ), and Wong et al ( 2021 )—and supports Bandura's argument to measure domain‐ and task‐specific SE, rather than general SE (Bandura, 1997 ).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the strong focus on breastfeeding, seen in the domain‐specific studies, implies that breastfeeding is critical for gaining confidence in parenting. The focus on breastfeeding mirrors the number of reviews regarding breastfeeding SE based on quantitative studies—such as Galipeau et al ( 2018 ), Gonzales ( 2021 ), Maleki et al ( 2021 ), and Wong et al ( 2021 )—and supports Bandura's argument to measure domain‐ and task‐specific SE, rather than general SE (Bandura, 1997 ).…”
Section: Discussionsupporting
confidence: 54%
“…Prenatal education for pregnant women with breastfeeding as its content could promote the development of their breastfeeding competency. Health education in the healthcare centers was more effective than in other departments in the hospital, which is reflecting the importance of pregnant women school in improving breastfeeding competency and behaviors 33 . The study showed that pregnant women can gain more perinatal knowledge www.nature.com/scientificreports/ through prenatal education provided by pregnant women school 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Konsisten dengan teori kognitif-sosial Bandura, self-efficacy sebagai proses dinamika kognitif mengevaluasi kepercayaan orang dan kemampuan mereka untuk melakukan perilaku sehat dan berkontribusi pada perilaku pencegahan mereka. Dennis berpendapat bahwa empat sumber penting termasuk pencapaian kinerja, pengalaman perwakilan, persuasi verbal, dan respons fisiologis dapat mengesankan tingkat kepuasan wanita (Dennis, 2003;Maleki, et al, 2021).…”
Section: Pembahasanunclassified